2005
DOI: 10.1111/j.1460-9592.2005.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Human factors in pediatric anesthesia incidents

Abstract: In our institution anesthetic human factors occur in 42.5% of in-theater incidents in pediatric anesthesia. Knowledge of these is necessary so that changes can be made in practice both by individuals and departments of anesthesia, to make anesthesia as safe as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 18 publications
3
56
2
7
Order By: Relevance
“…(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) The average annual rate of critical incident reporting at our hospital is 3%-4% (Fig. 2), and this percentage has remained stable through the years despite an increase in patient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) The average annual rate of critical incident reporting at our hospital is 3%-4% (Fig. 2), and this percentage has remained stable through the years despite an increase in patient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The background of the study was reported adverse events where some contributing factors had been identified as lack of appropriate airway management equipment and wrong use of or missing medications. Most anaesthesiologist will recognise such events in their clinical practice [111,112]. In 2007, we were not able to identify a validated methodology to develop and design specific medical safety checklists from previously published studies.…”
Section: Methodological Considerations and Ethics Validitymentioning
confidence: 98%
“…There are also taxonomies for particular aspects of practice such as medication error 26,27 or particular kinds of errors within particular areas of practice such as anaesthetic human errors. 28 The work of Reason provides a sound theoretical base for conceptualising and managing error. 1,6,7,9,10,[29][30][31][32][33][34][35][36] However, the need remains for research that can better contribute to the theorisation of hospital error in ways that are useful to policy and practice.…”
Section: Evidence-based Theorisation Useful To Policy and Practicementioning
confidence: 99%